Implement provisions on direct democracy in the 2013 Constitution - Nguyễn Tuấn Anh; Ngô Thị Nghĩa Bình (My University, 2023)
Implement provisions on direct democracy in the 2013 Constitution
Keywords: Direct democracy; 2013 Constitution; Legal implementation; Citizen rights